Carbide Twist Drill Spiral Groove Abrasive Flow Polishing and Abrasive Flow Analysis - Ji, Tian; Lu, Lintao; Ren, Boming; Bian, Guihong; Huang, Shengli (Manufacturing Technology Journal, 2024)
This paper carries out the simulation of abrasive flow for twist drill spiral grooves and the experimental study of abrasive flow polishing. The flow of abrasive in spiral groove in abrasive flow polishing twist drill was analyzed by CFD using FLUENT software. Different inlet speeds and abrasive concentrations were used as parameters for simulation calculations to obtain the state parameters of dynamic pressure and abrasive velocity in the flow channel, and to analyse their effects on the abrasive flow in the spiral groove. The analysis results show that the dynamic pressure in the twist drill spiral groove increases with the increase of inlet speed, and becomes smaller as the abrasive flows along the spiral surface. Under the condition of different abrasive concentrations, the velocity of abrasive decreases with the increase of abrasive concentration. Under the same abrasive concentration condition, the abrasive velocity decreases gradually from inlet to outlet. For actual processing, the abrasive concentration can be selected between 50-60%. Based on the simulation analysis results, the parameters of abrasive flow polishing process were set, the orthogonal test method was adopted, and the test data were analysed by the polar analysis method the results showed that the priority order of the influencing factors of spiral groove polishing was: abrasive type > inlet speed > polishing time. Using SiC abrasive, inlet speed 0.5 m.s-1, polishing time30 min, the surface roughness of the spiral groove of cemented carbide twist drill after polishing is the minimum, reaching Ra0.189, which is far less than the design requirements.
Keywords: Twist Drill Spiral Groove; CFD Analysis; AFM Polishing